Perkembangan Kurikulum Pendidikan Agama Islam di Indonesia: Studi Literatur pada Era Kolonial Hingga Era Reformasi - Azzahra Sabrina Hanifa; Yaniz Naura Naviana Haryadi; Khuriyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to describe the development of the Islamic Religious Education curriculum in Indonesia starting from the Dutch-Japanese colonial pre-independence period, the old order period, the new order period, the reformation period to the independent learning curriculum. The research in this article was carried out using the library research method. The type of research used by researchers is qualitative research. The results of this research show that the Islamic Religious Education (PAI) curriculum has always developed following the times, starting from the pre-independence era characterized by a colonial-style education system, the old order curriculum consisting of the 1947 curriculum, the 1952 curriculum and the 1964 curriculum, the new order curriculum. consisting of the 1968 curriculum, 1975 curriculum, 1984 curriculum, 1994 curriculum, reform period education curriculum consisting of KBK (2006), KTSP (2006), 2013 curriculum and the independent learning curriculum where each curriculum has its own characteristics in its implementation.